ChemInform Abstract: Vibrational Spectrum and Gas‐Phase Structure of Disulfur Dinitride (S2N2). Issue 48 (2nd December 2014) - Perrin, Agnes; Flores Antognini, Andrea; Zeng, Xiaoqing; Beckers, Helmut; Willner, Helge; Rauhut, Guntram
Abstract The first gas‐phase high‐resolution FTIR spectra of S2N2 (D2h) is presented together with a high‐level quantum mechanical and experimental study of its molecular ground‐state and equilibrium structures.